COMPARATIVE EFFECTS OF MAITLAND MOBILIZATION VERSUS MCKENZIE CERVICAL EXERCISE PROTOCOL ON PAIN, CERVICAL RANGE OF MOTION, AND PROPRIOCEPTION IN PATIENTS WITH CHRONIC NON-SPECIFIC MECHANICAL NECK PAIN: A RANDOMIZED CONTROLLED TRIAL (Journal of Medical & Health Sciences Review, 2025)
Background: Chronic non-specific mechanical neck pain is a prevalent musculoskeletal condition with multifactorial etiologies including poor posture, muscle imbalance, and joint dysfunction. Maitland mobilization and McKenzie exercises are two widely utilized physiotherapy interventions, yet evidence comparing their effects on pain, cervical range of motion (CROM), and proprioception is limited.Objective: To compare the effectiveness of Maitland Mobilization and McKenzie Cervical Exercise Protocol in reducing pain, improving cervical range of motion, and enhancing cervical proprioception in patients with CNMNP.Methodology: A single-blinded randomized controlled trial was conducted with 60 participants aged 25–50 years diagnosed with CNMNP. Participants were randomly assigned to Group A (Maitland mobilization + conventional therapy) or Group B (McKenzie protocol + conventional therapy). Pain (NPRS), CROM (goniometer), and cervical proprioception (laser pointer repositioning test) were measured at baseline and after 4 weeks of intervention.Results: Both groups showed statistically significant improvements in pain reduction, CROM, and proprioception (p